Alternatives to Acid Suppression Treatment for Laryngopharyngeal Reflux. (October 2020) - Huestis, Mikayla J.; Keefe, Katherine R.; Kahn, Chase I.; Tracy, Lauren F.; Levi, Jessica R.
Objective: Laryngopharyngeal reflux (LPR) and associated symptoms can be refractory to treatment with acid suppressing medication. We investigated the role and evidence for complementary and alternative medicine (CAM) for LPR in this systematic review. Review Methods: Complementary and alternative treatment was defined in this systematic review as any non-acid suppressing medication, treatment, or therapy. A literature search was performed by two authors in consultation with a medical librarian using controlled vocabulary for "complementary and alternative medicine" and "laryngopharyngeal reflux" in the databases PubMed and EMBASE, with supplemental searches with Google Scholar. Results: Twenty articles were included in this review for the modalities: alginate, diet modification, prokinetics, respiratory retraining, voice therapy, rikkunshito (RKT), hypnotherapy, and sleep positioning. The studies were analyzed for bias based on the Cochrane criteria for RCTs and Methodological Index for non-RCT (MINORS) criteria for all other studies. For each modality a level of evidence was assigned to the current body of evidence using the GRADE approach. Conclusion: There is mixed evidence with a high degree of bias and heterogeneity between studies for the modalities presented in the paper. Based on this review, an anti-reflux diet is recommended for all patients and there is some low-quality evidence to support alkaline water. For patients with predominant vocal symptoms there is evidence that supports voice therapy. There is insufficient evidence to recommend prokinetics at this time. For patients with predominant globus symptoms, alginate, RKT, and relaxation strategies may be used in conjunction with acid suppressing medications for symptom relief.